2020
DOI: 10.1002/anie.202009719
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Solid Solution Formation Triggers the Propagation of Homochirality

Abstract: Propagation of homochirality plays a crucial role in the discussion on the origin of life. We investigated the role of structurally related enantiopure additives in chiral symmetry breaking during reactive crystallizations. We demonstrate that symmetry breaking can be driven towards the same absolute configuration as the additive if this additive forms an enantiospecific solid solution with the racemate. We observe two antagonistic processes: enantiospecific growth inhibition directs symmetry breaking to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…X‐ray analysis of 12 supports this observation showing that racemic 12 crystallizes as a conglomerate (a mixture of enantiomerically pure crystals, with the overall solid being racemic [14f, 28] ) where in addition to hydrogen bonding between N−H and P=O moiety a non‐covalent halogen bond between bromine and the P=O moiety was observed (see Supporting Information for further details). We anticipate that this additional bonding might be responsible for the distinct crystallization behavior of both para ‐halogenated phosphoramidates 11 and 12 making them not suitable substrates for chiral amplification using our preferred dissolution method although we did not observe the reverse that is, solid phase [5, 7a–d,g] amplification (vide infra for amino acid 21 ).…”
Section: Methodsmentioning
confidence: 88%
“…X‐ray analysis of 12 supports this observation showing that racemic 12 crystallizes as a conglomerate (a mixture of enantiomerically pure crystals, with the overall solid being racemic [14f, 28] ) where in addition to hydrogen bonding between N−H and P=O moiety a non‐covalent halogen bond between bromine and the P=O moiety was observed (see Supporting Information for further details). We anticipate that this additional bonding might be responsible for the distinct crystallization behavior of both para ‐halogenated phosphoramidates 11 and 12 making them not suitable substrates for chiral amplification using our preferred dissolution method although we did not observe the reverse that is, solid phase [5, 7a–d,g] amplification (vide infra for amino acid 21 ).…”
Section: Methodsmentioning
confidence: 88%
“…Additionally, to investigate the possibility of forming mixed crystals with optically active valine, the crystals obtained from recrystallization in the presence of valine were analyzed by NMR spectroscopy. It was found that valine was not included in the crystals of 1 …”
Section: Resultsmentioning
confidence: 99%
“…Amplification of this enantioimbalance using Viedma ripening offers a mechanism for the propagation of homochirality. [30] Moreover, a detailed study of the initial symmetry breaking that occurs during grinding a slurry of racemic conglomerate in the presence of a high additive loading (20 wt%) confirmed that two antagonistic processes occur simultaneously during this stage: enantiospecific growth inhibition and enantiospecific solid solution formation (Figure 1). [30] The resulting ee detected in the liquid and solid phases corresponds to the difference in the relative contributions of these two processes.…”
mentioning
confidence: 89%
“…Remarkably, even a low additive loading (i. e. 5 wt%) is sufficient to direct deracemization towards the configuration of the additive. [30] Nevertheless, it remains unclear whether the initial symmetry breaking follows the pathway identical to that observed with a high additive loading (Figure 2), or if the contributions of the solid solution formation take over the contributions of the enantiospecific growth inhibition.…”
mentioning
confidence: 98%